How Do Households Choose Their Employer-Based Health Insurance? - Jean Marie Abraham; William B. Vogt; Martin S. Gaynor (SAGE Publishing, 2006)
Using the 1996 Medical Expenditure Panel Survey, this study estimates a model of household demand for employer-based health insurance to investigate the set of plan and household characteristics that influence coverage choices. Overall, we find that households are sensitive to price with respect to their coverage decisions, and that price sensitivity varies by marital status, wealth, and the number of offers of employer coverage available to the household. We also find that lower-income households are less likely to select an option that provides coverage for all household members. Using our model estimates, we simulate the effect of employers offering various levels of "opt-out" payments on changes in workers' probabilities of not taking up coverage and on expected costs.